Meningkatkan aktifitas dan hasil belajar peserta didik melalui model pembelajaran Teams Games Tournament (TGT) menggunakan media “ATM BCA” - Sutrisno Sutrisno (Jurnal Teori dan Praksis Pembelajaran IPS, 2019)
Learning models or media that are appropriate to the characteristics of the material, and students can increase the effectiveness of learning. Models that can involve students can improve understanding of the material and the same conditions also apply to media that are by the characteristics of the material. Teams Games Tournament (TGT) learning model using the media "ATM BCA" through the steps: (1) Information, (2) Grouping, (3) Planning, (4) Acting, (5) Organizing, (6) Presenting and Reward, (7) Evaluating is an effort to achieve that goal. This research is action research carried out in two cycles, each cycle consisting of two meetings. The results of this study indicate that the activities and learning outcomes of students have increased significantly.DOI: 10.17977/um022v4i22019p074